An observational study of safety and clinical outcome measures across patient groups in the United Kingdom Medical Cannabis Registry. Issue 3 (4th March 2023) - Olsson, Fabian; Erridge, Simon; Tait, James; Holvey, Carl; Coomber, Ross; Beri, Sushil; Hoare, Jonathan; Khan, Shaheen; Weatherall, Mark W; Platt, Michael; Rucker, James J; Sodergren, Mikael H
ABSTRACT: Background: There is a paucity of high-quality data on patient outcomes and safety after initiating treatment with cannabis-based medicinal products (CBMPs). The aim of this study was to assess the clinical outcomes and safety of CBMPs by analyzing patient-reported outcome measures and adverse events across a broad spectrum of chronic conditions. Research design and methods: This study analyzed patients enrolled in the UK Medical Cannabis Registry. Participants completed the EQ-5D-5L to assess health-related quality of life, Generalized Anxiety Disorder-7 (GAD-7) questionnaire to measure anxiety severity, and the Single-item Sleep Quality Scale (SQS) to rate sleep quality at baseline and follow-up after 1, 3, 6, and 12 months. Results: A total of 2833 participants met inclusion criteria. The EQ-5D-5L index value, GAD-7, and SQS all improved at each follow-up (p < 0.001). There was no difference in EQ-5D-5L index values between former or current illicit cannabis consumers and naïve patients (p > 0.050). Adverse events were reported by 474 (16.73%) participants. Conclusions: This study suggests that CBMPs are associated with an improvement in health-related quality of life in UK patients with chronic diseases. Treatment was tolerated well by most participants, but adverse events were more common in female and cannabis-naïve patients.